Habermas, Islam, and theorizing the "Other" - Sheedy, Matt (Critical research on religion, 2018)
Over the last twenty years, Jürgen Habermas has been at the forefront of debates involving religion in the public sphere. In the wake of 9/11 he has responded to the problems of terrorism, "radical Islam," and the so-called Muslim question in Europe, attempting to align these issue with his broader theories of deliberative democracy and postsecularism. Although Habermas aims for an inclusive model of deliberation in the public sphere, I argue that his reliance on macro theories of secularization and modernization reproduce an ideal of secular liberal democracy as the standard by which to think about various "Others," including Muslims. As a result, I claim that he ends up reproducing a soft variety of the "clash of civilizations" thesis by failing to account for the complexity of Muslim identities. In conclusion, I look at alternative models that are better able to historicize and contextualize "Islam" in the past and present, and point to significant gaps that must be filled if his proposals are to be taken seriously.